Konseling Shalat Dhuha Dalam Membentuk Akhlak - Ainur Rofiq (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims is to determine and describe the implementation of dhuha prayer, as a form of moral development and describe the implementation of dhuha prayer as a form of moral development. Dhuha prayer is one type of prayer that is highly recommended to be done consistently by Muslims, dhuha prayer offers many privileges, advantages for Muslims who are consistent in doing it, one of the privileges of this worship is that it can make it easier to get sustenance. This method is a qualitative method, this is a study used to examine objects by providing examples directly, providing examples with slow, moderating reading, and giving examples and attention. Based on the results of this study, it can be concluded that: The application of counseling techniques through Dhuha Prayer can form morals that are embedded in a person so important to realize. In addition to providing teaching in the community, there are activities as habits that are routinely carried out to improve self-quality, personality, and behavior. In carrying out coaching there are inhibiting factors. Supporting factors. Inhibiting factors are divided into external factors and internal factors. External factors from outside such as, rain in the morning and others. Internal factors are factors within a person such as someone is bored in following the implementation, lying and others. In overcoming obstacles all members have worked together well. The method used in following up is adjusted to the obstacles and problems that occur in a person himself. While the influence of carrying out the Dhuha Prayer on a personality that contains moral values, such as being able to create a sense of peace, increase cooperation, respect differences, and strengthen the attitude of istiqomah in a person.